2021
DOI: 10.1186/s13063-021-05463-7
|View full text |Cite
|
Sign up to set email alerts
|

Rationale and study design of an early care, therapeutic education, and psychological intervention program for the management of post-intensive care syndrome and chronic pain after COVID-19 infection (PAIN-COVID): study protocol for a randomized controlled trial

Abstract: Background Critically ill patients with COVID-19 are an especially susceptible population to develop post-intensive care syndrome (PICS) due to acute respiratory distress syndrome (ARDS). Patients can suffer acute severe pain and may have long-term mental, cognitive, and functional health deterioration after discharge. However, few controlled trials are evaluating interventions for the prevention and treatment of PICS. The study hypothesis is that a specific care program based on early therapeu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…However, a meta‐analysis of 10 RCTs has reported that post‐ICU physical rehabilitation may not necessarily improve health and mental quality of life at 6‐ to 12‐month 136 . Nonetheless, more RCTs are ongoing that sought to test other potential non‐pharmaceutical therapies (e.g., neuromuscular electrical stimulation, virtual reality and rehabilitation programs) for post‐ICU survivors of COVID‐19 137–141 …”
Section: Resultsmentioning
confidence: 99%
“…However, a meta‐analysis of 10 RCTs has reported that post‐ICU physical rehabilitation may not necessarily improve health and mental quality of life at 6‐ to 12‐month 136 . Nonetheless, more RCTs are ongoing that sought to test other potential non‐pharmaceutical therapies (e.g., neuromuscular electrical stimulation, virtual reality and rehabilitation programs) for post‐ICU survivors of COVID‐19 137–141 …”
Section: Resultsmentioning
confidence: 99%
“…We included adult patients who were admitted to the Intensive Care Unit (ICU) for SARS-CoV-2 infection from April to December 2020. From an initial cohort of 102 COVID-19 survivors that were evaluated one-month follow-up after hospital discharge by the PAIN-COVID protocol (see ( Ojeda et al, 2021 )); 58 COVID-19 survivors agreed to participate in our study and were assessed 6 months after hospital discharge (See Flowchart 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…The study was approved by the Ethics Committee of the Hospital Clinic of Barcelona (approval number HCB/2020/0549) on 14 May 2020. The study protocol has been submitted for publication (Ojeda et al, 2021 ). Participants were enrolled 1 month after hospital discharge after giving their written informed consent.…”
Section: Methodsmentioning
confidence: 99%